2022
DOI: 10.1002/app.52208
|View full text |Cite
|
Sign up to set email alerts
|

Nafion/SiO2@TiO2‐palygorskite membranes with improved proton conductivity

Abstract: This work deals with the synthesis of SiO2@TiO2 supported palygorskite fibers and their use as a filler for proton exchange membrane fuel cells in order to improve their performance. SiO2@TiO2‐palygorskite nanostructured particles were synthesized separately with original route to ensure the growth of TiO2 and then of SiO2 on the surface of the clay. Accordingly, the introduction of the synthetic filler (SiO2@TiO2‐paly) into the electrolyte membrane (Nafion) aims to improve mechanical, thermal, and proton cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
4
6
0
Order By: Relevance
“…The literature showed that the induction of inorganic fillers, including SiO 2 and TiO 2 , enhanced the acid retention capability. , Our findings are in agreement with previous studies. , It is important to remember that the unique chemical structure of imidazole was linked to its notable PA doping capability. Generally, doping a membrane with more PA molecules increases its proton conductivity because of the more dynamic hydrogen-bond networks; however, this comes at the membrane’s mechanical strength and swelling costs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The literature showed that the induction of inorganic fillers, including SiO 2 and TiO 2 , enhanced the acid retention capability. , Our findings are in agreement with previous studies. , It is important to remember that the unique chemical structure of imidazole was linked to its notable PA doping capability. Generally, doping a membrane with more PA molecules increases its proton conductivity because of the more dynamic hydrogen-bond networks; however, this comes at the membrane’s mechanical strength and swelling costs.…”
Section: Resultssupporting
confidence: 92%
“…43 The literature showed that the induction of inorganic fillers, including SiO 2 and TiO 2 , enhanced the acid retention capability. 90,91 Our findings are in agreement with previous studies. 92,93 It is important to remember that the unique chemical structure of imidazole was linked to its notable PA doping capability.…”
Section: Oxidative Stabilitysupporting
confidence: 94%
“…The incorporation of radical scavengers/quenchers (i.e., CeO 2 , TiO 2 , ZrO 2 , MnO 2 , and other metal oxides) into the PEM or CLs has been effective in mitigating the decomposition rate of the PEM. However, a serious drawback has been recognized in the use of radical scavengers based on redox reactions of transition-metal cations; i.e., the ion exchange of the metal cations such as Ce 3+ lowered the σ H of the electrolyte, both the membrane itself and the ionomer in the cathode CL, resulting in severe polarization loss. , Thus, it is of the utmost importance to escape the trade-off between the PEM durability and output performance that exists for the radical scavengers employed so far.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 nanoparticles are widely available due to their inexpensiveness and high mechanical strength, good electrochemical resistance, and thermal stability, [35][36][37] enabling them to maintain stability in high voltage and acidic environments characteristic of PEMWE. In this work, we choose TiO 2 as the filler.…”
Section: Preparation Of Composite Nafion Membranementioning
confidence: 99%